Bioinformatic and biochemical studies point to AAGR-1 as the ortholog of human acid alpha-glucosidase in Caenorhabditis elegans - Sikora, Jakub; Urinovská, Jana; Majer, Filip; Poupetová, Helena; Hlavatá, Jitka; Kostrouchová, Marta; Ledvinová, Jana; Hrebícek, Martin (Molecular and cellular biochemistry, 2010)
Human acid alpha-glucosidase (GAA, EC 3.2.1.20) is a lysosomal enzyme that belongs to the glycoside hydrolase family 31 (GH31) and catalyses the hydrolysis of alpha-1,4- and alpha-1,6-glucosidic linkages at acid pH. Hereditary deficiency of GAA results in lysosomal glycogen storage disease type II (GSDII, Pompe disease). The aim of this study was to assess GH31 proteins in Caenorhabditis elegans (C. elegans) to identify the ortholog of human GAA. Bioinformatic searches for GAA ortholog in C. elegans genome revealed four acid alpha-glucosidase-related (aagr-1-4) genes. Multiple sequence alignment of AAGRs with other GH31 proteins demonstrated their evolutionary conservation. Phylogenetic analyses suggested clustering of AAGR-1 and -2 with acid-active and AAGR-3 and -4 with neutral-active GH31 enzymes. In order to prove the AAGRs' predicted alpha-glucosidase activity, we performed RNA interference of all four aagr genes. The impact on the alpha-glucosidase activity was evaluated at pH 4.0 (acid) and pH 6.5 (neutral), with or without the inhibitor acarbose. AAGR-1 and -2 expressed acidic alpha-glucosidase activity; on the contrary, AAGR-3 not -4 represented the predominant neutral alpha-glucosidase activity in C. elegans. Similar results were obtained in each of aagr-1 and -4 deletion mutants. Moreover, based on our structural models of AAGRs and these biochemical experiments, we hypothesize that the enzymatic sensitivity of AAGR-2 and human maltase-glucoamylase to the inhibitor acarbose is associated with a tyrosine residue in the GH31 active site, whereas acarbose resistance of AAGR-1 and human GAA is associated with the corresponding tryptophane in the active site. Acid-active AAGR-1 may thus represent the ortholog of human GAA in C. elegans.
Keywords: Caenorhabditis elegans Proteins; Glycoside Hydrolase Inhibitors; Animals; lidé; alpha-Glucosidases; inhibitory glykosidových hydrolas; Phylogeny; akarbóza; Computational Biology; alfa-glukosidasy; katalytická doména; proteiny Caenorhabditis elegans; Sequence Alignment; zvířata; sekvenční seřazení; fylogeneze; výpočetní biologie; Catalytic Domain; Acarbose; Humans